2018
DOI: 10.17796/1053-4628-42.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Dental Decay and Oral Findings in Children and Adolescents Affected by Different Types of Cerebral Palsy: A Comparative Study

Abstract: Dental caries was an important issue in mixed and athetoid CP groups. Oral habits and malocclusions were the most significant oral health problems in individuals with CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 24 publications
1
13
1
6
Order By: Relevance
“…Rodrigues et al . associated the different types of CP to the severity of dental caries and other oral findings including periodontitis in children and adolescents, where they concluded that mixed and athetoid CP groups have highest incidence of dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…Rodrigues et al . associated the different types of CP to the severity of dental caries and other oral findings including periodontitis in children and adolescents, where they concluded that mixed and athetoid CP groups have highest incidence of dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in fascicle lengths and fibre diameters were seen with the muscle fibres [22]. The muscular coordination is very important in performing the day to day activities like taking care of the oral hygiene [23]. Moreover, the interaction or cooperation of two or more muscles are known to produce a combined effect greater than the sum of their separate effects.…”
Section: Muscle and Cpmentioning
confidence: 99%
“…En México se necesitan datos epidemiológicos actualizados de niños y adolescentes con parálisis cerebral infantil. 3,6,7 A. Causas de la parálisis cerebral infantil La primera estrategia del odontopediatra es la obtención de una historia médica detallada para conocer la situación del paciente, investigando las causas de la parálisis y las complicaciones secundarias.…”
Section: Para Entender La Parálisis Cerebralunclassified
“…Comúnmente con riesgo de fracturas dentales en el esmalte y la dentina. 7,22 En términos generales no hay producción excesiva de saliva, pero sí sialorrea secundaria a patrones anormales en la deglución, disfunción oromotora e incompetencia labial. Con riesgo de aspiración (por un mal manejo de secreciones) e irritación cutánea perioral.…”
Section: Conocimiento De Las Características Bucodentales En Paráunclassified
See 1 more Smart Citation